Genes & signals - Ptashne Mark; Gann Alexander (New York Cold Spring Harbor Laboratory Press, 2002)
Genes and Signals analyzes gene regulation from a new perspective. The first chapter describes mechanisms found in bacteria, and two subsequent chapters discuss which of these is most highly exploited in higher organisms. A final chapter relates these mo
Keywords: Genetic regulation